2021
DOI: 10.3390/v13020236
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HEV IgG Avidity Testing: Utility for Diagnosing Acute and Resolved Genotype 3 Infections

Abstract: European Association of the Study of the Liver (EASL) guidelines specify HEV RNA, as well as anti-HEV IgG and IgM as positive markers for acute HEV infection. HEV RNA assay sensitivity limitations may lead to false negative test results in patients with low levels of viremia. Moreover, anti-HEV IgM positivity is not a reliable indicator for distinguishing between acute and resolved infections given the ability of this antibody to persist several months after a resolved infection. Our study aims were to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…This change was observed in France [28,30], England [31,32], Belgium [33], Germany [34], and Netherlands [35]. In other countries, such as Italy and Spain [36], the 3e and 3f subtypes are still predominant [37,38]. Recent studies suggested differences in the pathogenicity of the subtypes [34,39], but results are still debate since some others do not remark the same correlation [40].…”
Section: Introductionmentioning
confidence: 99%
“…This change was observed in France [28,30], England [31,32], Belgium [33], Germany [34], and Netherlands [35]. In other countries, such as Italy and Spain [36], the 3e and 3f subtypes are still predominant [37,38]. Recent studies suggested differences in the pathogenicity of the subtypes [34,39], but results are still debate since some others do not remark the same correlation [40].…”
Section: Introductionmentioning
confidence: 99%